2016
DOI: 10.1128/aem.01373-16
|View full text |Cite
|
Sign up to set email alerts
|

A New Catabolic Plasmid in Xanthobacter and Starkeya spp. from a 1,2-Dichloroethane-Contaminated Site

Abstract: ABSTRACT1,2-Dichloroethane (DCA) is a problematic xenobiotic groundwater pollutant. Bacteria are capable of biodegrading DCA, but the evolution of such bacteria is not well understood. In particular, the mechanisms by which bacteria acquire the key dehalogenase genes dhlA and dhlB have not been well defined. In this study, the genomic context of dhlA and dhlB was determined in three aerobic DCA-degrading bacteria (Starkeya novella strain EL1, Xanthobacter autotrophicus strain EL4, and Xanthobacter flavus strai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 57 publications
0
7
0
Order By: Relevance
“…The initial dehalogenase was isolated and crystallized, revealing for the rst time the enzymatic mechanism of a fundamental reaction in organic chemistry: the S N 2 nucleophilic displacement reaction of an alkylhalide with water. 21 The structures also showed that the haloalkane dehalogenases are members of a large group of related enzymes, the a/b-hydrolase fold family, which also includes lipases and [22][23][24][25][26] The dehalogenase gene is plasmid localized, and a plasmid was also found in other organisms that grow on DCA. [23][24][25][26] These dehalogenases catalyze cofactor-independent hydrolytic reactions.…”
Section: Use and Biodegradation Of 12dichloroethanementioning
confidence: 99%
See 2 more Smart Citations
“…The initial dehalogenase was isolated and crystallized, revealing for the rst time the enzymatic mechanism of a fundamental reaction in organic chemistry: the S N 2 nucleophilic displacement reaction of an alkylhalide with water. 21 The structures also showed that the haloalkane dehalogenases are members of a large group of related enzymes, the a/b-hydrolase fold family, which also includes lipases and [22][23][24][25][26] The dehalogenase gene is plasmid localized, and a plasmid was also found in other organisms that grow on DCA. [23][24][25][26] These dehalogenases catalyze cofactor-independent hydrolytic reactions.…”
Section: Use and Biodegradation Of 12dichloroethanementioning
confidence: 99%
“…30 A chloroacetate dehalogenase gene has also been found on a plasmid. 26 Genes encoding catabolic enzymes for synthetic compounds are oen located on plasmids, frequently associated with transposons or insertion elements which enable gene transfer or gene activation. Insertion elements also ank regions encoding haloalkane dehalogenase.…”
Section: Use and Biodegradation Of 12dichloroethanementioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, haloalkane dehalogenases are also widely present in organisms and ecosystems with no track record of degrading synthetic organohalogens (Hesseler et al, 2011; Chaloupkova et al, 2014; Guan et al, 2014; Carlucci et al, 2016; Weigold et al, 2016), suggesting a role in the metabolism of natural halogenated compounds. Another intriguing observation is that identical dehalogenase genes are repeatedly obtained by classical enrichment using synthetic compounds whereas these genes do not appear in general genomic databases (Poelarends et al, 1998; Poelarends et al, 2000; Govender and Pillay, 2011; Munro et al, 2016), indicating that enrichment identifies a widely distributed subpopulation of dehalogenase-producing organisms that does not represent the majority of the dehalogenase activity present in natural environments. These specific dehalogenase genes may be widespread: identical 1,2-dichloroethane dehalogenase (DhlA) genes were discovered in the Netherlands, South Africa, Korea, and Australia.…”
Section: Aerobic Metabolism Of Organochlorine Compoundsmentioning
confidence: 99%
“…These specific dehalogenase genes may be widespread: identical 1,2-dichloroethane dehalogenase (DhlA) genes were discovered in the Netherlands, South Africa, Korea, and Australia. However, they are located on different plasmids and associated with different insertion sequences, illustrating the high mobility of the genes (Song et al, 2004; Munro et al, 2016). The mechanism of distribution and the ancestry of 1,2-dichloroethane isolates remain unknown.…”
Section: Aerobic Metabolism Of Organochlorine Compoundsmentioning
confidence: 99%